Introversion and the American Jewish Condition: A Critical Examination of Shimon Halkin’s "Until the Crisis" - Amaar mohmad hattab ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The notion of identity has remained one of the most prominent thematic threads in modern Hebrew literature, perhaps even its greatest preoccupation. The reader often encounters this theme explicitly manifested in various creative works, while at other times detecting it subtly woven into the fabric of the literary text. One such exemplary novel that has deeply grappled with the ramifications of this question is "Until the Crisis", published in 1929. What sets this work apart, however, is the novelist’s virtuosic deployment of techniques such as the interior monologue, dialogue, temporal structuring, and stream of consciousness - all in a concerted effort to plumb the depths of his characters’ psyches and render the feelings of isolation and introversion that they harbor, for these are among the most salient expressions of self, identity, and belonging. It appears that these motifs of isolation and introversion were pervasive features within the Jewish collective consciousness. Accordingly, the novelist conscientiously, with a sense of fairness and objectivity, sets out to elucidate this emotional and existential disposition across diverse strata of his fictional society, transcending the boundaries of social, intellectual, or material standing. In doing so, he seems to be articulating what was regarded as a defining characteristic of the Jewish experience - the arduous journey of self-affirmation. Moreover, the novel is considered ahead of its time and a pioneering achievement in the creative realm, particularly in its treatment of the crises afflicting the Jewish psyche. This thematic quality is discernible from the very threshold of the title, and further reverberates throughout the literary fabric. Should the researcher succeed in framing the novel within this interpretive lens, they would be equally justified in ascribing to the novelist a remarkable creative aptitude in diagnosing the vulnerabilities and frailties inherent in the Jewish character, as well as his trailblazing innovations in the artistic techniques deployed in his literary output - elements that compel the researcher to delve deeper into the novel’s substantive and formal dimensions.